Mapping the Landscape of Data Collection: A Reflection on the Dynamics of Fieldwork in Qualitative Research - Subedi, Khim Raj (KMC Journal, 2024)
This study explores the complexities of qualitative fieldwork and unpacks the fieldwork dynamics drawing on critical reflections based on the experiences of interviewing primary level teachers in exploring their identities. I argue that qualitative fieldwork is not a one-shot, linear activity but a negotiated and relational task requiring a flexible and context-specific plan. This study identifies challenges associated with the fieldwork relating to establishing and sustaining a good relationship and reciprocity between the researcher and the participants, unequal power dynamics between the researcher and the participants, participants’ familiarity with and habitual response to the survey questionnaires, narrow understanding of confidentiality and anonymity as ethical considerations, unmatched gender between the researcher and the participants, and through and detailed capture of micro field jottings and writing the fieldnotes. I suggest initiating fieldwork with sufficient informal conversation and establishing a rapport to gain the participants’ trust, positioning oneself as an insider to acquire valuable and meaningful data.Fieldwork